Environmental fungicides and triazole resistance in Aspergillus. Issue 2 (5th December 2013) - Bowyer, Paul; Denning, David W
Abstract Fungal diseases are problematic in both human health and agriculture. Treatment options are limited and resistance may emerge. The relatively recent recognition of triazole resistance in Aspergillus fumigatus has prompted questioning of the origin of resistance. While multiple mechanisms are described in clinical isolates from triazole‐treated patients, some de novo resistance is also recognised, especially attributable to TR34/L98H. Such strains probably arose in the environment, and, indeed, multiple studies have now demonstrated TR34/L98H triazole resistance strains of A. fumigatus from soil. Docking and other in vitro studies are consistent with environmental resistance induction through exposure to certain triazole fungicides, notably difenoconazole, propiconazole, epoxiconazole, bromuconazole and tebuconazole. This article addresses the potential implications of this issue for both human health and food security. © 2013 Society of Chemical Industry